2017
DOI: 10.1017/s1463423617000433
|View full text |Cite
|
Sign up to set email alerts
|

‘You started something … then I continued by myself’: a qualitative study of physical activity maintenance

Abstract: Background: Most mid-life and older adults are not achieving recommended physical activity (PA) targets and effective interventions are needed to increase and maintain PA long-term for health benefits. The Pedometer And Consultation Evaluation (PACE-UP) trial, a three-armed primary care pedometer-based walking intervention in those aged 45-75 years, demonstrated increased PA levels at 12 months. A three-year follow-up was conducted to evaluate long-term PA maintenance, including a qualitative component. Aim:To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
9
16
0
Order By: Relevance
“…As for the barriers to PA, this study is in agreement with prior work, confirming that lack of time and unfavorable weather conditions are the most common barriers for increasing and maintaining PA (Brawley, Rejeski, & King, 2003;Kelly et al, 2016;Normansell et al, 2014;Trost, Owen, Bauman, Sallis, & Brown, 2002;Wahlich et al, 2017). In addition, two participants explicitly expressed their preference of sedentary lifestyle and lack of motivation as a barrier to increase their PA levels.…”
Section: Results In the Context Of Other Literaturesupporting
confidence: 89%
“…As for the barriers to PA, this study is in agreement with prior work, confirming that lack of time and unfavorable weather conditions are the most common barriers for increasing and maintaining PA (Brawley, Rejeski, & King, 2003;Kelly et al, 2016;Normansell et al, 2014;Trost, Owen, Bauman, Sallis, & Brown, 2002;Wahlich et al, 2017). In addition, two participants explicitly expressed their preference of sedentary lifestyle and lack of motivation as a barrier to increase their PA levels.…”
Section: Results In the Context Of Other Literaturesupporting
confidence: 89%
“…The importance of involving others in initiating and maintaining physical activity has been widely reported [28,30,32]. Our study showed that family members and friends were facilitators, and in particular, spouses who joined the patient, which concurs with other studies [28,29,33,34].…”
Section: Discussionsupporting
confidence: 92%
“…Patients perceived physical and emotional benefits of their increased physical activity, which positively affected their engagement in increasing and maintaining their activity; this has also been found in other studies [28,30]. Patients’ increased awareness also engaged them to continue and maintain being physically active [2831].…”
Section: Discussionsupporting
confidence: 70%
“…The lack of interest shown by members of this group regarding physical activity may be an indicator to the managers of fitness centres that strategically they should not develop specific programs to them, since it would be very difficult to change their inactivity behaviour. Wahlich et al, 2017, suggest the use of technologic devices, such pedometer or caloric expenditure measurements as strategies to increase this segment engagement on fitness club.…”
Section: Discussionmentioning
confidence: 99%